Perbaikan Kualitas Citra Untuk Klasifikasi Daun Menggunakan Metode Fuzzy K-Nearest Neighbor - Asih Setiyorini; Jayanti Yusmah Sari (Ultimatics : Jurnal Teknik Informatika, 2017)
Plants have many benefits for human life such as food, medicine, industry, environmental protection, even oxygen provider for other organisms. To know the types of plants is necessary. Classification of plants can be done with additional features of leaves in these plants. In determining whether or not the image identification process is needed a process of image quality improvement. Improved image quality is used to prepare the image in an ideal form so as not to cause problems and interpellation results as well. In this research the method used is Fuzzy K-Nearest Neighbor (FKNN) method. The Fuzzy K-Nearest Neighbor (FKNN) method is the most objective method. Based on the results of experiments conducted, Fuzzy K - Nearest Neighbor (FKNN) modeling method was obtained for 93% completeness. Keywords-Image quality improvement, Fuzzy KNearest Neighbor (FKNN)